An Empirical Exploration of Demand and Supply in Malaysia Housing Market - Alom, Shahedin (South Asian Journal of Social Sciences and Humanities, 2020)
The article provides an overview of factors that affect the supply of housing and the level of demand on the basis of market change in the Malaysia with transition economy. In the last decade, home prices in Malaysia have fluctuated considerably. This market volatility creates a significant impact on the Malaysian who want to buy or invest housing. Several scholars have argued that housing prices are directly correlated to buyers’ ability to own a home, so the government plays a pivotal role in ensuring Malaysia’s housing prices are equivalent to income rates. Therefore, this study is aimed at addressing various factors that impact Malaysian housing prices. The dynamics of prices on land and various types of completed buildings are also discussed. In this paper, it is seen how the housing market in Malaysia has been long discussed and has given attention to a great extent since the First Malaysia Plan (1966- 1970). The finding presented in this paper may help to convince investor and house buyers that market volatility is not necessarily something to fear. The housing market is, to a certain degree predictable and hence house price movement may be detectable in advance.